Design of a Computerized Fence at Nyabikoni Campus Kabale University. - Rugabanomwe, Arnold (Kabale University, 2023)
This proposal is about a design of a computerized fence for Kabale University Nyabikoni Campus. The writing here in this report contain five chapters: Chapter one; Is the introduction of the proposal that states the contents of the background of the project and the scope? Chapter two; Contains the literature review, works and related information by other scholars about design mainly architectural working drawings. Chapter three; Outlines the methodology of how the project will be done; these are sequential methods for the process, Chapter four; Discusses the results of the project that involve details of the budget, work plan, appendices and reference, Chapter five; Future or prospective works recommendations, conclusions and references (bibliography)